A look to the future acidified ocean through the eyes of the alien and invasive alga Caulerpa cylindracea (Chlorophyta, Ulvophyceae). Issue 6 (2nd November 2022) - Santin, Anna; Moschin, Emanuela; Lorenti, Maurizio; Buia, Maria Cristina; Moro, Isabella
ABSTRACT: Underwater CO2 vents represent natural laboratories where the responses of marine organisms to ocean acidification can be tested. In a such context, we investigated the changes in the physiology, anatomy, and ultrastructure of the non-indigenous algal species Caulerpa cylindracea growing along a natural pH/CO2 gradient, by conducting a reciprocal transplant experiment between two populations from an acidified vs a non-acidified site. Stress effects in transplants from current to lowered pH conditions resulted in a decrease in the number of active chloroplasts together with an increased number of dilatations between thylakoid membranes and a higher amount of plastoglobules. These changes were consistent with a decrease in the chlorophyll content and in photosynthetic efficiency, matched by an increase in carotenoid content and non-photochemical yields. On the opposite side, transplants from low to current pH showed a recovery to original conditions. Unexpectedly, no significant difference was recorded between wild populations living at current and lowered pH. These results suggest an ongoing acclimation process to lowered pH in the C. cylindracea populations growing in the vent area. This confirms the high plasticity of this invasive species, able to cope not only with different light and temperature conditions but even with a new acidified scenario.